Knowledge and Compliance of Iron and Folic Acid Supplementation among Pregnant & Postnatal Women in a Hospital of Kathmandu - Mishra, Rupesh Kumar; Tiwari, Kalpana (Journal of Advanced Academic Research, 2020)
The high prevalence of iron deficiency anemia and low compliance of iron and folic acid supplementation was reported among pregnant women in Nepal. This study aimed to determine the knowledge and compliance of iron and folic acid supplementation among pregnant and postnatal women in Kathmandu. A descriptive cross-sectional study design was adopted for the study. Sample size was 103 and purposive sampling technique was used to collect the data. All Pregnant women of having above 7 month pregnancy and postnatal’s up to 6 months women were included. Data was collected by using self-administered questionnaire .All the obtained data were analyzed with the help of SPSS version 20. Assessment of knowledge revealed that 85.6 % (88) of the participants have adequate knowledge regarding iron and folic acid supplementation .The findings showed 78.6% (81) of the respondents had iron and folic acid compliance as standard of Nepal government that is to be taken minimum 180 tablet before delivery. It concludes that the level of knowledge and compliance rate of iron and folic acid supplementation in Kathmandu is satisfactory in comparisons to national status i.e. 42% according to Nepal Demographic health survey 2016. Pearson chi-square test shows that level of knowledge on iron and folic acid tablet is not associated with the compliance of iron and folic acid tablet (χ²= 0.019, p< 0.889). The main reason of respondents having compliance is due to having proper counseling from health worker and non compliance is due to forgetting to have tablet. Therefore improving knowledge level only can’t improve compliance level, various factors like counseling, accessibility and availability of iron and folic acid tablet, side effect of tablet and family support also affects the compliance of iron and folic acid supplementation.